Atypical Kawasaki Disease in a Two-Year-Old Girl with Initial Presentation of Acute Diarrhea - Situmorang, Desman; Karina, Permata P (Journal of Medicine and Health, 2021)
Kawasaki Disease is a spectrum of idiopathic, self-limited fever disease affecting children under 5 years old. This disorder can be challenging to be diagnosed by a pediatrician since there is no specific diagnostic laboratory test. One atypical Kawasaki Disease case presented with gastrointestinal symptoms, a two-year-old girl was hospitalized with fever, accompanied by non- hemorrhagic diarrhea three days before admission. Physical examination revealed unilateral cervical lymph enlargement and mild-moderate dehydration. Initial laboratory examination result showed thrombocytosis, leukocytosis (shift to the left), and normal routine fecal analysis. The patient was initially diagnosed with acute diarrhea with mild-moderate dehydration. She was treated with a rehydration regimen and antibiotic, but her fever persisted. On the third day of hospitalization, she fulfilled 3 of the classic Kawasaki Disease criteria (conjunctivitis, cracked lips with strawberry tongue, and lymphadenopathy). Further blood work resulted in increased C- reactive protein 43.35 mg/L and ESR 72 mm/hour, while chest X-ray and electrocardiograph were within normal limit. This patient was proceed to Hasan Sadikin General Hospital for further examination and therapy. Atypical Kawasaki Disease can be a puzzling diagnosis due to its uncommon presentations. Clinicians should importantly keep it in mind as a differential diagnosis in patients with prolonged fever. Keywords: atypical Kawasaki disease; diarrhea; prolonged fever